Association of the Affordable Care Act's Medicaid Expansion With Care Quality and Outcomes for Low-Income Patients Hospitalized With Heart Failure. Issue 7 (July 2018) - Wadhera, Rishi K.; Joynt Maddox, Karen E.; Fonarow, Gregg C.; Zhao, Xin; Heidenreich, Paul A.; DeVore, Adam D.; Matsouaka, Roland A.; Hernandez, Adrian F.; Yancy, Clyde W.; Bhatt, Deepak L.
Abstract : Background: Heart failure (HF) is the leading cause of morbidity and mortality in the United States. Despite advancement in the management of HF, outcomes remain suboptimal, particularly among the uninsured. In 2014, the Affordable Care Act expanded Medicaid eligibility, and millions of low-income adults gained insurance. Little is known about Medicaid expansion's effect on inpatient HF care. Methods and Results: We used the American Heart Association's Get With The Guidelines–Heart Failure registry to assess changes in inpatient care quality and outcomes among low-income patients (<65 years old) hospitalized for HF after Medicaid expansion, in expansion, and nonexpansion states. Patients were classified as low-income if covered by Medicaid, uninsured, or missing insurance. Expansion states were those that implemented expansion in 2014. Piecewise logistic multivariable regression models were constructed to track quarterly trends of quality and outcome measures in the pre (January 1, 2010–December 31, 2013) and postexpansion (January 1, 2014–June 30, 2017) periods. These measures were compared between expansion versus nonexpansion states during the postexpansion period. The cohort included 58 804 patients hospitalized across 391 sites. In states that expanded Medicaid, uninsured HF hospitalizations declined from 7.9% to 4.4%, and Medicaid HF hospitalizations increased from 18.3% to 34.6%. Defect-free HF care was increasing during the preexpansion period (adjusted odds ratio/quarter, 1.06; 95% confidence interval, 1.03–1.08) but did not change after expansion (adjusted odds ratio, 0.99; 95% confidence interval, 0.97–1.02). Patterns were similar for other quality measures. There were no quality measures for which the rate of improvement sped up after expansion. In-hospital mortality rates remained similar during the preexpansion (adjusted odds ratio, 0.99; 95% confidence interval, 0.96–1.02) and postexpansion periods (adjusted odds ratio, 1.00; 95% confidence interval, 0.97–1.03). Among nonexpansion states, uninsured HF hospitalizations increased (11.6% to 16.7%) as did Medicaid HF hospitalizations (17.9% to 26.6%), and no quarterly improvement was observed for most quality measures in the post compared with preexpansion period. During the postexpansion period, defect-free care and mortality did not differ between expansion and nonexpansion states. Conclusions: Medicaid expansion was associated with a significant decline in uninsured HF hospitalizations but not improvements in quality of care or in-hospital mortality among sites participating in a national quality improvement initiative. Efforts beyond insurance expansion are needed to improve in-hospital outcomes for low-income patients with HF. Abstract : Supplemental Digital Content is available in the text.